Implikasi Penanaman Nilai-Nilai Filosofi Pendidikan Multikultural Bagi Siswa Hindu SMPN 2 Basarang Kabupaten Kapuas - Gunawan, I Gede Dharman; Juni Arta, I Gede Arya (Jurnal Penelitian Agama Hindu, 2024)
It is very important to instill the values ​​of a multicultural educational philosophy from an early age in schools. Considering that Indonesia is an archipelagic country consisting of various ethnicities, races, cultures and religions. This is done as a preventive effort to minimize and prevent conflicts that arise due to various differences. By instilling the values ​​of a multicultural education philosophy in schools, including SMPN 2 Basarang, Kapuas Regency, it is hoped that this can become a strategic effort to maintain the diversity that exists in Indonesia. Efforts to instill the values ​​of a multicultural educational philosophy are important to be implemented at SMPN 2 Basarang, Kapuas Regency, considering the diverse cultures of the students. This research aims to examine the implications of efforts to instill multicultural educational philosophy values ​​for Hindu students at SMPN 2 Basarang, Kapuas Regency. The method used in this research is a qualitative method in the form of narrative text, ideas, words obtained from data sources. Based on the results of the research that has been carried out, it can be seen that there are several implications of instilling the values ​​of a multicultural educational philosophy for students at SMPN 2 Basarang, Kapuas Regency, namely: the implications of unity values, the implications of togetherness values, the implications of harmony values, the implications of diversity values, and the implications of values pluralism. It can be concluded that these five value implications bring direct changes to the understanding, characteristics and behavior of students at SMPN 2 Basarang, Kapuas Regency in viewing diversity. Such as, strengthening attitudes of tolerance, mutual respect for different beliefs and cultures, cooperation and concern for each other.